Hydrogen Sulfide Attenuates Atherosclerosis in a Partially Ligated Carotid Artery Mouse model via Regulating Angiotensin Converting Enzyme 2 Expression - Lin, Yanjun; Zeng, Huasu; Gao, Lin; Gu, Ting; Wang, Changqian; Zhang, Huili (Frontiers in Physiology, 2017)
Hydrogen sulfide has been suggested to play an essential role in atherogenesis. There is a paucity of information about the association between H2S and angiotensin converting enzyme 2 (ACE2), a novel homologue of ACE. Therefore, the aim of the study was to explore the role of H2S in atherosclerosis with respect to ACE2 both in vitro and in vivo. Here, a murine model of acutely disturbed flow-induced atherosclerosis by left common carotid artery (LCA) partial ligation was utilized. We found that carotid partial ligation in high-fat fed apoE-/- mice significantly inhibited endogenous H2S synthesis in LCA. Application of NaHS, an H2S donor considerably attenuated the severity of atherosclerosis with upregulating carotid expression of ACE2, thus converting pro-atherosclerotic angiotensin II (Ang II) to anti-atherosclerotic angiotensin 1-7 (Ang-(1-7)). The anti-atherosclerotic effect of NaHS was dramatically abolished by treatment with MLN-4760, an ACE2 inhibitor. In contrast, blockage of H2S formation by DL-propargylglycine exacerbated the burden of atherosclerotic plaques accompanied by inhibiting carotid expression of ACE2. At the cellular level, NaHS dose-dependently promoted the expression of ACE2 and conversion from Ang II to Ang-(1-7) in unstimulated or LPS-stimulated endothelial cells, thus exerting anti-inflammatory properties. The anti-inflammatory effect of NaHS was abrogated by pretreatment with DX600, a selective ACE2 inhibitor. In conclusion, these data provide direct evidences that endogenous H2S insufficiency exists in acute flow disturbance-induced atherosclerosis and that application of H2S may protect against atherosclerosis via upregulating ACE2 expression in endothelial cells.